ANALISIS RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Izza Ashsifa; Muhammad Teguh Kuncoro; Naila Rizki Salisa (TECHNOBIZ : International Journal of Business, 2023)
This study aims to analyze financial ratios' ability to predict a company's financial distress. The data used are data on industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021 with a total sample of 108 samples. The dependent variable, financial distress, is measured using the interest coverage ratio (ICR) indicator. Independent variables, liquidity measured using the current ratio (CR), profitability using return on assets (ROA), and leverage measured using the debt-to-equity ratio (DER). The moderation variable in this study is company size. This study used logistic regression analysis and MRA. The results of the study using logistic regression tests showed that leverage had a positive effect on financial distress, while liquidity and profitability did not affect financial distress. Based on the MRA test, company size is able to moderate the effect of leverage on financial distress. In contrast, the company size is unable to moderate the effect of liquidity and profitability on financial distress. This research contributes to investors who can use this model by incorporating financial ratio indicators to assess a company's financial health before making investment-related decisions Keywords: financial distress, liquidity, profitability, leverage, company size